Seabather's eruption: report of fourteen cases - ANDRÉ LUIZ ROSSETTO; FÁBIO LANG DA SILVEIRA; ANDRÉ CARRARA MORANDINI; VIDAL HADDAD JUNIOR; CHARRID RESGALLA JUNIOR (Anais da Academia Brasileira de Ciências, 2015)
Seabather's eruption is a papulo-pruritic dermatitis caused by the nematocysts of the larvae of the jellyfish Linuche unguiculata retained in the clothing fibers. Previously reported in Brazil, this work describes fourteen cases that occurred in the State of Santa Catarina, in southern Brazil. The new cases observed over a short period of time (the first half of January, 2012), at the height of the summer season, should alert health teams to possible epidemics on the coast of the state of Santa Catarina.